Survei Deteksi Dini Keseimbangan pada Anak-Anak Suku Laut Duana di RT. 01 RW. 04 Kelurahan Tanjungbatu Kota - Rahmi Windhy Astari; Cici Anggraini (Syntax Corporation Indonesia, 2021)
In children of age experiencing an increase in the quality of physical activity ability, in addition, it can also experience delays in growth and development. The World Health Organization (WHO) provides a statement that the most common childhood health disorders are musculoskeletal disorders. The musculoskeletal system has an important role in maintaining the balance of the human body. Balance is a major factor in maintaining and maintaining the balance of the human body properly. The purpose of the study was todetermine early detection of balance in children ofthe duana sea tribe. The research method conducted is quantitative research using survey methods with stork balance check instruments balance stand test. Sampling techniques using purposive sampling methods. Each child is tested 3 times and is taken the best grades. The time during the test is calculated using the Stopwatch. The results of the study measured the balance of children of the duana sea tribe, namely men 74% and women 58% got a very good category with the highest percentage results. This means that the children of the duana sea tribe are able to maintain a very good balance. The conclusion of early childhood motor development research is related to the development of motorik and with itsability to move. Children's motor skills can be seen from various movements and games that are done every day. Themotor skills of early childhood are closely related to the activities carried out by children.